Post-Release Monitoring of Diet Profile and Diet Quality of Reintroduced African Buffalo (Syncerus Caffer) in Umfurudzi Park, Zimbabwe. (September 2014) - Muposhi, Victor K.; Chanyandura, Admire; Gandiwa, Edson; Muvengwi, Justice; Muboko, Never; Taru, Philip; Kupika, Olga L.
Post-release monitoring of wildlife is essential to the success of ecological restoration initiatives. Translocation of wildlife to new ecosystems is associated with changes in diet profiles of individuals and ultimately animal performance, since productivity of rangelands varies in time and space. The population decline and local extinction of buffalo and other species in Umfurudzi Park, Zimbabwe, in the late 1980s led to temporary suspension of hunting activities. Recently, efforts have been made to resuscitate Umfurudzi Park through wildlife reintroductions and active ecosystem management. We assessed the diet profile and diet quality of the African buffalo ( Syncerus caffer ) between 2011 and 2012. A total of 42 grass species constituted the diet spectrum of buffalo. Heteropogon contortus, Eragrostis racemosa, Steroechlaena tenuifolia and Themeda triandra contributed significantly to the buffalo diet during the four seasons of the study period. Although a wide spectrum of grass species was selected in the wet season, the diversity of grass species selected was not significantly different among the seasons. Grass species crude protein deteriorated from 4.5% in the wet season to 3.5% in the dry season. Crude protein and phosphorus levels in buffalo faecal samples were within the recommended nutrient scale for southern Africa large herbivores. We conclude that feed availability and quality may not be limiting the persistence of the reintroduced buffalo. There is a need to closely monitor grass availability, dietary shifts, and forage quality over time, as well as resource partitioning with other feeding guilds.